21st-century teachers: The students’ perspectives - Maida Norahmi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2017)
The issues regarding the demands of creative, innovative, and professional teachers are certainly on the concern of stakeholders and practitioners in education. Substantial efforts were conducted by the government to meet the 21st-century teachers having the four competencies required for being a teacher and coping with the needs of modern education. A survey research was conducted to collect respondents’ opinion as the main source of data to describe whether the 21st-century teachers are on the demands and to gain information that the students have a similar perception to teacher’s competencies required by the government. Seventy-five questionnaires related to the competencies were given to students of English Education Study Program of 2013 to 2016. The questionnaires were aimed at collecting written information dealing with what the students perceived towards the activities implemented by teachers in the process of teaching and learning. The result of questionnaire analysis revealed that most students expected the 21st-century teachers to have skills in teaching and in connecting it with the development of today’s technology and today’s student characteristics. The data also showed that the students constructed the same characteristics of teacher’s competencies required by the government regarding pedagogy, personality, sociality, and professionality.